2007
DOI: 10.1152/physiol.00012.2007
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Dysfunction in Obesity: A Potential Mechanism in the Pathogenesis of Obesity-Associated Insulin Resistance and Hypertension

Abstract: Obesity is an important risk factor for insulin resistance and hypertension and plays a central role in the metabolic syndrome. Insight into the pathophysiology of this syndrome may lead to new treatments. This paper has reviewed the evidence for an important role for the microcirculation as a possible link between obesity, insulin resistance and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
241
2
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(255 citation statements)
references
References 132 publications
6
241
2
6
Order By: Relevance
“…It has been proposed, as in muscle, 32 that FFA elevation impairs insulin-mediated activation of PI3-kinase and increases the production of reactive oxygen species, leading to impairment of nitric oxide production and consequently, altered vasodilation. 15 Microvascular rarefaction is also a hallmark of hypertension; the difference in arterial pressure between MetS and control subjects could contribute to the lower CD in patients with MetS. In addition, increased release of endothelin-1, a major vasoconstrictor substance, is likely.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been proposed, as in muscle, 32 that FFA elevation impairs insulin-mediated activation of PI3-kinase and increases the production of reactive oxygen species, leading to impairment of nitric oxide production and consequently, altered vasodilation. 15 Microvascular rarefaction is also a hallmark of hypertension; the difference in arterial pressure between MetS and control subjects could contribute to the lower CD in patients with MetS. In addition, increased release of endothelin-1, a major vasoconstrictor substance, is likely.…”
Section: Discussionmentioning
confidence: 99%
“…15 Excess secretion of proinflammatory cytokines, such as tumor necrosis factor-a, and decreased production of anti-inflammatory adipokines, such as adiponectin, may also play a role in small-arterial vasculature dysfunction. 15 In a human endothelial cell model, tumor necrosis factor-a has been shown to reduce the expression of endothelial NO synthase, resulting in decreased NO synthesis 33,34 and increased ET-1 expression. 35 In addition, sympathetic neural activation, resulting in higher vasomotor tone, may also contribute to vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14] The progression and persistence of obesity have been associated with a progressive alteration of the function and the structure of the vascular wall, including chronic inflammation, endothelial dysfunction, alteration of vascular tone and reactivity, proliferation of smooth muscle cells, neo-angiogenesis and altered patterns of blood flow regulation with both hypertensive and arteriosclerotic consequences. [15][16][17] Some of the metabolic, endocrinologic and hemodynamic changes associated with obesity and hypertension are partially reversed by BW reduction, which decreases BP in overweight non-obese hypertensive patients. Numerous trials of hypertension treatment have shown that weight loss, whether alone or in combination with antihypertensive drugs, has a beneficial effect on BP control.…”
Section: Introductionmentioning
confidence: 99%